Parrots consume sodium-rich palms in the sodium-deprived landscape of the Western Amazon Basin - Brightsmith, Donald J. (2017)
Herbivorous animals face shortages of different minerals in different geographic areas. In the Amazon Basin, sodium is often limiting, driving herbivores to seek supplemental sources. In the lowlands of the western Amazon Basin, parrots commonly consume sodium-rich soils at clay licks but lick use varies widely among species, and to date, parrots in the region have not been reported consuming other supplemental sodium sources. We document 11 species of psittacines consuming sodium-rich leaves and trunks of Attalea butyracea palms growing on sodium-rich soils in lowland Peru. Consumed palms had more sodium and less potassium than uneaten A. butyracea palms and other palm species in the area. Among A. butyracea palm parts, sodium and Na:K ratios were highest in trunks (consumed by parrots in 94% of the 387 foraging bouts recorded) and lowest in leaves (consumed in only 14% of foraging bouts). The low potassium and high Na:K ratio suggest that birds may be seeking not just any sodium sources, but those low in potassium, as potassium is known to exacerbate dietary sodium shortages. Use of the palms and species' abundance in the study area were not correlated. Instead, parrot species that consumed palms the most were those that use relatively few traditional soil clay licks. This finding suggests that parrot species in the region have fundamental differences in preferred strategies for obtaining supplemental sodium and may help explain documented interspecific differences in geophagy.